Embedding viral hepatitis into primary healthcare: results of a strategic landscape analysis in Vietnam and the Philippines - Bethany Holt; Martin Fernandez; Dang Nguyen; Danica Delima; Lam Dam Duy; Manu Gaspar; Geohari Hamoy; Bao Ngoc Le; Jan Llevado; Joseph Michael D. Manlutac; Jhaki Mendoza; Timothy Mercado; et al. (Elsevier, 2024)
Summary: Chronic viral hepatitis is a significant public health concern in the Western Pacific, including in Vietnam and the Philippines. To accelerate progress toward meeting the 2030 elimination goals, the World Health Organization (WHO) encourages countries to adopt an integrated, people-centered health sector response to hepatitis, grounded in Primary Health Care (PHC). A review of the academic and grey literature, along with policy documents, was conducted to describe the national health system and PHC response to hepatitis B and C in Vietnam and the Philippines. Information was analyzed against the four strategic levers of the WHO Operational Framework for PHC to identify challenges and opportunities. The findings suggest that both countries have relatively robust policy frameworks, with some room for improvement. Vietnam may have stronger political commitment and funding than the Philippines, while the Philippines appears to be stronger in community engagement. Both countries share challenges and opportunities for learning to actualize viral hepatitis elimination utilizing a PHC approach.